1997
DOI: 10.1128/jb.179.18.5744-5750.1997
|View full text |Cite
|
Sign up to set email alerts
|

Identification and nitrogen regulation of the cyanase gene from the cyanobacteria Synechocystis sp. strain PCC 6803 and Synechococcus sp. strain PCC 7942

Abstract: An open reading frame (slr0899) on the genome of Synechocystis sp. strain PCC 6803 encodes a polypeptide of 149 amino acid residues, the sequence of which is 40% identical to that of cyanase from Escherichia coli. Introduction into a cyanase-deficient E. coli strain of a plasmid-borne slr0899 resulted in expression of low but significant activity of cyanase. Targeted interruption of a homolog of slr0899 from Synechococcus sp. strain PCC 7942, encoding a protein 77% identical to that encoded by slr0899, resulte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
48
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 34 publications
(41 reference statements)
3
48
0
Order By: Relevance
“…AB005890). Although the tsp for cynABDS has not been reported, the expression of these genes, tested with a cynS probe, has been shown to be NtcA dependent (43).…”
Section: A Survey Of Ntca-activated Genesmentioning
confidence: 99%
See 2 more Smart Citations
“…AB005890). Although the tsp for cynABDS has not been reported, the expression of these genes, tested with a cynS probe, has been shown to be NtcA dependent (43).…”
Section: A Survey Of Ntca-activated Genesmentioning
confidence: 99%
“…strain PCC 7942, cynS is clustered together with three genes, cynABD, which might encode an ABCtype transporter. Cyanase activity and cynS and its accompanying genes are subject to repression by ammonium (43).…”
Section: Genes Of Nitrogen Assimilation Pathways Rendering Intracellumentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Espie et al (2007) reported an abundance of cyanate transport genes among bacteria. An ABC-type transporter for cyanate was identified in the freshwater cyanobacteria Synechococcus elongatus strain PCC7942 (Harano et al 1997) and Synechococcus sp. strain PCC6301.…”
mentioning
confidence: 99%
“…A number of Synechococcus and Prochlorococcus strains grow on cyanate as the sole N source (Miller and Espie 1994;Kamennaya et al 2008;Kamennaya and Post 2010). Cyanase (Enzyme Commission [EC] 4.2.1.104), first characterized in Escherichia coli (Anderson 1980;Harano et al 1997), catalyzes a reaction of cyanate with bicarbonate producing ammonium and carbon dioxide. Growth on cyanate as the sole N source requires its transport over the cell membrane followed by its conversion to ammonium.…”
mentioning
confidence: 99%